2017
DOI: 10.1016/j.physleta.2017.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Permutation entropy based time series analysis: Equalities in the input signal can lead to false conclusions

Abstract: The following work is licensed under a Creative Commons: Attribution-NonCommercial-NoDerivatives 4.0 International (CC BY-NC-ND 4.0) License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 77 publications
(92 reference statements)
3
88
0
Order By: Relevance
“…Another major problem is regarding the computation of permutation entropy, which omits repeated consecutive values. This deficiency was admitted by the authors in a later paper [11].…”
Section: Information Theory Featuresmentioning
confidence: 87%
“…Another major problem is regarding the computation of permutation entropy, which omits repeated consecutive values. This deficiency was admitted by the authors in a later paper [11].…”
Section: Information Theory Featuresmentioning
confidence: 87%
“…Permutation entropy (PE) [33] is an algorithm based on time series phase space reconstruction and neighborhood value comparison, which can effectively describe the complexity of the system. PE has the advantages of simple algorithm, fast computing speed, and reliable calculation results [34]. MPE is an improved algorithm based on PE.…”
Section: Optimized Dmd Modes Via Mpementioning
confidence: 99%
“…If d is too large, the reconstruction of phase will homogenize the time series, which is not only time-consuming but also unable to reflect the small changes of the sequence. Bandt [33] and Zunino [34] suggested that d should be in the range 3-7. Time delay τ has little effect on the MPE of time series [35,36], and in most literatures [36][37][38], authors employ τ = 1.…”
Section: Optimized Dmd Modes Via Mpementioning
confidence: 99%
See 1 more Smart Citation
“…If some ordinal patterns appear more frequently than others, the PE decreases, indicating that the signal is less random and more predictable [30]. For convenience, H p is typically normalized with log m!, namely,…”
Section: Permutation Entropymentioning
confidence: 99%